2022
DOI: 10.2478/bsrj-2022-0019
|View full text |Cite
|
Sign up to set email alerts
|

Digital Competencies in Selected European Countries among University and High-School Students: Programming is lagging behind

Abstract: Background: Constant integration of digital technologies in economic and social life is rapidly and significantly shaping and changing our environment and ourselves. To function in such a world, even in daily routines, it is necessary to possess certain digital competencies. Objectives: This paper aims to examine how university and high-school students of economic orientations from selected European countries self-assess their digital competencies, and to analyse the identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The authors of [12] report a positive outlook on digital competencies, especially in information and data literacy, but underscore the need for more training, particularly for female and rural students. The findings of [13] complement this, revealing that university and high-school students self-assess their digital skills as below intermediate, with programming as a weak point. The authors of [14], on one hand, highlight the value academics place on students' digital competences for learning, while [15] points out the lack of a systematic process for developing these competencies in university environments, suggesting the need for a new strategic approach.…”
Section: Introductionsupporting
confidence: 55%
“…The authors of [12] report a positive outlook on digital competencies, especially in information and data literacy, but underscore the need for more training, particularly for female and rural students. The findings of [13] complement this, revealing that university and high-school students self-assess their digital skills as below intermediate, with programming as a weak point. The authors of [14], on one hand, highlight the value academics place on students' digital competences for learning, while [15] points out the lack of a systematic process for developing these competencies in university environments, suggesting the need for a new strategic approach.…”
Section: Introductionsupporting
confidence: 55%
“…A study by the University of Extremadura (Spain) [45] in 2017 already highlighted the need for better integration of ICTs to improve their use, that is, the improvement of digital competences. Subsequently, research conducted at the University of Zagreb (Croatia) [46] identified the fact that that the least-developed competences (with scores from 1 to 3) are: programming (1.37), creation and problem-solving (1.53), and searching, downloading, and filtering digital information and data (1.71). Finally, the study by the University of Guajira (Colombia) [27] in 2022 showed that constant table and chart creation is carried out by only 46.4%, presentation development by 62.9%, and collaborative work by 67.5%; all of this through the use of digital devices.…”
Section: Discussionmentioning
confidence: 99%
“…Digital analysis refers to the process of examining, interpreting, and deriving insights from digital data and information. It involves the application of analytical tools and techniques to understand patterns, trends, and relationships within digital datasets (Draganac et al, 2022).…”
Section: Digital Analysis (Da)mentioning
confidence: 99%
“…The concept of digital analysis is crucial for making informed decisions, identifying opportunities, and addressing challenges in the digital environment (Draganac et al, 2022).…”
Section: Digital Analysis (Da)mentioning
confidence: 99%